STRATEGI PENGEMBANGAN TAMAN WISATA BOON PRING ANDEMAN SEBAGAI KAWASAN EKOWISATA DI KABUPATEN MALANG - Soelistyari, Hesti Triana; Alfian, Rizki; Kebkole, Metusalak Otnial (BUANA SAINS, 2023)
The Boon Pring Andeman Tourism Park area is an area that has the potential to develop into a tourist destination in Malang Regency. The condition of the unspoiled ecosystem can be utilized as a potential in developing the Boon Pring Andeman Park area as an ecotourism area in Malang Regency. The aim of this study is to determine in developing the Boon Pring Andeman Tourism Park area as one of the ecotourism areas in Malang Regency is to support an aggressive growth policy (Growth-oriented strategy) by utilizing the strengths and opportunities that exist in the Boon Pring Andeman Tourism Park area. By collaborating with government agencies, universities, and also the community around the Boon Pring Andeman Tourism Park area, we can increase the potential and overcome problems so that the quality of the park and the ecosystem around the area can be maintained so that the authenticity of the area is maintained so that there will be more and more tourists around the area as well as from outside Malang Regency who is interested in coming for a tour at the Boon Pring Andeman Tourism Park. In developing the tourism area, it is necessary to identify the potential and constraints and analyze the needs of visitors then present a new tourist area design by considering the culture around the park area as a basic concept so that it can produce tourism that can provide benefits including visual, aesthetic and educational which can improve tourists and regional income